2020
DOI: 10.15405/epsbs.2020.03.183
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of Renewable Energy Generation On The Cost Of Electricity Companies

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A comparative analysis of other regions indicated that creative funding and global collaboration could overcome these obstacles and advance Mozambique's renewable energy economy. The need to provide energy security and reduce environmental effects is what ignites interest in renewable energy sources (Morina, Balomenou, & U. Ergün, 2021;Voyko, 2020). The energy industry of Mozambique is vital to the country's economy since it supplies necessary inputs for all economic activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative analysis of other regions indicated that creative funding and global collaboration could overcome these obstacles and advance Mozambique's renewable energy economy. The need to provide energy security and reduce environmental effects is what ignites interest in renewable energy sources (Morina, Balomenou, & U. Ergün, 2021;Voyko, 2020). The energy industry of Mozambique is vital to the country's economy since it supplies necessary inputs for all economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Both strong economic arguments and environmental advantages are driving the switch to renewable energy. When government programs and policies are in place, renewable energy can improve competitiveness and provide financial gains (Voyko, 2020). The combination of renewable energy with financial technology (fintech) implies that financial advances can support the long-term growth of these enterprises (Jiang, 2023).…”
Section: Introductionmentioning
confidence: 99%